The first case report of a large deletion of the BRCA1 gene in Croatia: A case report. Issue 48 (December 2017) - Musani, Vesna; Sušac, Ilona; Ozretić, Petar; Eljuga, Domagoj; Levanat, Sonja
Abstract: Rationale: Breast cancer is one of the most common cancers in women, and it is the leading cause of cancer related deaths in Croatia. BRCA1 and BRCA2 gene mutations are the most common cause of hereditary breast cancer. Patient concerns: In this report we describe a Croatian patient with no apparent family history of cancer, who developed breast cancer first at 29, and again at 33. Diagnosis: Due to the early development of first breast cancer and triple negative status of the second, the attending physician suspected a hereditary aspect. Interventions: Patient was sent to BRCA1 genetic testing. Subsequently, her mother and sister were sent to check for the mutation found in the patient. Outcomes: BRCA1 exons 4-6 deletion was determined and sequencing confirmed the deletion as NG_005905.2:g.107648_117905del10257. Mother and sister were not affected, but since there were no available family members on the fathers' side, it was not possible to determine if this was a case of de novo mutation. Until now, only in three reports with the similar mutation the exact mutation borders were determined. The mutation in this case was not the same as previously reported and was more than twice in size. Lessons: All large deletions should be described at the nucleotide level, so that in cases with missing family data it would be possible to deduce if the mutation is already known. If the mutation is already known, it is probably not a de novo event, since it is unlikely that the breakpoints would be exactly the same more than once.